Tradução do ser e da verdade em José Marinho e Molière - Marinho, Cristina (2018)
Theatre, beyond its original mystery and yet in itself, contains, according to José Marinho’s meditation, the human, intimate drama, the pungent experience of looking for non representable truth. As a convention representing the world, itself representing other worlds, Theater clarifies, in the same large, baroque Molière’s way, the same debate about truth and lie, Poetry and Philosophy confounded, light and shadow images altogether; Marinho’s liberating criticism converges with classical literary renovated canon as far as both destroy a schematic tradition, hostile towards margins, through lucid, uncertain questions. Marinho evokes a verse from L’Avare, he transforms it, developing freely Reason refusing its’ totalitarianism in order to see what Molière’s lovers can see of life and joy, thanks to their love.